Against their will : the secret history of medical experimentation on children in cold war America - Hornblum, Allen M. (Palgrave Macmillan, 2013)
"The sad history of young children, especially institutionalized children, being used as cheap and available test subjects - the raw material for experimentation - started long before the atomic age and went well beyond exposure to radioactive isotopes. Experimental vaccines for hepatitis, measles, polio and other diseases, exploratory therapeutic procedures such as electroshock and lobotomy, and untested pharmaceuticals such as curare and thorazine were all tested on young children in hospitals, orphanages, and mental asylums as if they were some widely accepted intermediary step between chimpanzees and humans. Occasionally, children supplanted the chimps. Bereft of legal status or protectors, institutionalized children were often the test subjects of choice for medical researchers hoping to discover a new vaccine, prove a new theory, or publish an article in a respected medical journal. Many took advantage of the opportunity. One would be hard-pressed to identify a researcher whose professional career was cut short because he incorporated week-old infants, ward-bound juvenile epileptics, or the profoundly retarded in his experiments. In short, involuntary, non-therapeutic, and dangerous experiments on children were far from an unusual or dishonorable endeavor during the last century"--